Polymorphism identification and characterisation within candidate genes for scrapie susceptibility in sheep - Shook, Kerida Stephanie; Justus Liebig University Giessen (My University, 2014)
Certain polymorphisms in the prion protein gene (PRNP) gene have been shown to modulate classical and atypical scrapie susceptibility in sheep. Sheep carrying the ARR/ARR genotype seem more resistant to classical scrapie whereas the VRQ haplotype greatly increases classical scrapie susceptibilty. Classical scrapie has been reported in one ARR/ARR sheep and with the advent of active surveillance in the EU, not only have two other ARR/ARR sheep with classical scrapie been identified, but also atypical scrapie was shown to be more prevalent than expected. Haplotypes increasing susceptibility to atypical scrapie, such as AHQ or AF141RQ, contrast with those of classical scrapie. It has been estimated that PRNP is responsible for approximately 79% of the genetic influence of PRNP on classical scrapie susceptibility.The goal of the study was to identify single nucleotide polymorphisms (SNPs) in candidate genes for scrapie susceptibility and test them for association with both classical and atypical scrapie susceptibility in sheep. Five candidate genes, LAMR1, SCRG1, PRND, RTN4 and VIM, were chosen due to their locations within or near mouse quantitative trait loci (QTL) for scrapie susceptibility. The ovine candidate genes were then amplified and sequenced. Sequences attained for LAMR1, SCRG1, PRND, and VIM were submitted to GenBank.A synonymous C/T LAMR1 SNP analysed is located in Exon 6 at the third nucleotide position of codon 232. For the SCRG1, PRND and RTN4 genes, a G/A SNP (Intron1), a T/C SNP (3 -UTR) and a G/A SNP (Intron 7) could be identified. None of these mutations were found to be located in a functional or regulatory site within noncoding regions. For each candidate gene, one SNP was tested for possible association with scrapie status using DNA samples from an established scrapie DNA bank held at the Institute of Animal Breeding and Genetics, Justus-Liebig-University, Giessen, Germany.Genotyping was accomplished using restriction fragment length polymorphism (RFLP) or amplification-created restriction site (ACRS)-RFLP analyses. For the LAMR1, SCRG1 and RTN4 SNPs, DNA samples from up to 106 classical scrapie positive sheep as well as up to 137 healthy flock mates were genotyped. In the atypical scrapie group, DNA samples from up to 93 atypical scrapie positive sheep and up to 304 healthy flock mates were genotyped. Since PRND is located near the PRNP gene on ovine chromosome (OAR) 13, positive and negative DNA samples were matched for PRNP genotype. For the PRND SNP, 56 DNA samples each from both classical and atypical scrapie positive sheep were genotyped. Negative controls consisted of DNA samples from 74 healthy flock mates from classical scrapie herds and 73 healthy flock mates from atypical scrapie herds. For each of the SNPs investigated in this study, no significant differences in allele or genotype frequencies were observed for classical or atypical scrapie positive groups when compared to healthy flock mate control groups. Although one SNP was identified in the ovine VIM gene, sequence information available at that time indicated a pseudogene had been amplified. Since, updated sequence information for bovine VIM shows that the synonymous C/T SNP identified in this study is located at the first position of codon 43. No significant associations between candidate gene SNPs and scrapie status could be shown. Due to the low numbers of animals genotyped for the association studies, these genes cannot be excluded as candidate genes for scrapie susceptibility in sheep.With the development of the Illumina Ovine SNP50 BeadChip, it would be possible to use the chip to identify SNPs associated with scrapie susceptibility. However, sample size needs to be increased in order to identify genetic loci that have modest effects on scrapie susceptibility in sheep. This could be accomplished by combining various scrapie DNA banks from different EU countries.

Bestimmte Polymorphismen des Prionenproteingens (PRNP) besitzen einen Einfluss auf die Empfänglichkeit für klassische und atypische Scrapie beim Schaf. Träger des ARR/ARR Genotyps scheinen mehr Resistenz gegenüber klassische Scrapie zu besitzen, wohingegen der VRQ Haplotyp die Empfänglichkeit erhöht. Allerdings wurde in einem Schaf mit ARR/ARR Genotyp klassische Scrapie nachgewiesen, und mit der Einführung der aktiven Überwachung in der EU sogar in zwei weiteren Schafen mit ARR/ARR Genotyp. Die aktive Überwachung hat zudem gezeigt, dass die Prävalenz von atypischer Scrapie höher ist als erwartet. Haplotypen wie z.B. AHQ und AF141Q, welche die Empfänglichkeit für atypische Scrapie erhöhen, wirken sich im Gegensatz hierzu unterschiedlich auf die Empfänglichkeit für klassische Scrapie aus. 79% der Empfänglichkeit für klassischer Scrapie werden dem PRNP Gen zugeschrieben, die übrigen 21% anderen, unbekannten Faktoren. Das Ziel dieser Studie war es, SNPs (single nucleotide polymorphism) in Kandidatengenen für Scrapie Empfänglichkeit zu identifizieren, und diese auf Assoziationen sowohl mit klassischer als auch atypischer Scrapie zu überprüfen. Hierfür wurden 5 Kandidatengene, LAMR1, SCRG1, PRND, RTN4 and VIM aufgrund ihrer Lokalisation in Maus QTLs (quantitative trait loci) für Scrapie Empfänglichkeit ausgewählt. Anschließend wurden diese Gene im Schaf amplifiziert und sequenziert. Die ermittelten Sequenzen von LAMR1, SCRG1, PRND, und VIM wurden elektronisch bei der GenBank eingereicht.Der C/T LAMR1 SNP konnte im Exon 6 an der dritten Position von Kodon 232 lokalisiert werden. Für die SCRG1, PRND und RTN4 Gene wurden entsprechend ein A/G SNP (Intron 1), T/C SNP (3 -UTR) und ein G/A SNP (Intron 7) identifiziert. Keiner dieser drei SNPs war in einem funktionellen oder regulatorischen Bereich innerhalb der nicht-kodierenden DNA lokalisiert. Jeweils einer der für LAMR1, SCRG1, PRND und RTN4 identifizierten SNPs wurde anschließend mit Hilfe der Scrapie DNA Bank (Institut für Tierzucht und Haustiergenetik, Justus-Liebig-Universität, Giessen) auf eine Assoziation mit Scrapiestatus getestet. Die Genotypisierung erfolgte mittels RFLP (restriction fragment length polymorphism) oder ACRS (amplification-created restriction site)-RFLP Analyse. Für die LAMR1, SCRG1 und RTN4 SNPs wurden DNA Proben von bis zu 106 auf klassische Scrapie positiv getestete Schafe sowie bis zu 137 gesunden Herdenmitglieder zur Genotypisierung verwendet. Für die atypische Scrapie Gruppe wurden DNA Proben von bis zu 93 positiv getesteten Schafen und bis zu 304 gesunden Herdenmitgliedern zur Genotypisierung verwendet. Da PRND stromabwärts vom PRNP Gen auf dem ovinen Chromosom 13 lokalisiert ist, stimmten Scrapie positive und negative Proben hinsichtlich ihrer PRNP Genotyps überein. Für den PRND SNP wurden von jeder klassischen und atypischen Scrapie positiven Gruppe jeweils 56 Proben genotypisiert. Als Negativkontrolle dienten Proben von 74 Herdenmitglieder bei klassischer Scrapie und 73 Herdenmitglieder bei atypischer Scrapie. In Hinblick auf Empfänglichkeit für klassische oder atypische Scrapie konnten keine signifikanten Assoziationen der Allel- oder Genotypfrequenzen gefunden werden.Ein SNP wurde in dem VIM Gen identifiziert. Zum Zeitpunkt dieser Studie deutete die Sequenzinformation daraufhin, dass ein Pseudogen amplifiziert wurde. Neue Sequenzerkenntnisse zeigten allerdings dass der synonyme C/T SNP auf der ersten Position des Kodons 43 lokalisiert ist. Obwohl keine Assoziationen nachgewiesen worden sind, bleiben die untersuchten Kandidatengene interessant in Hinblick auf Scrapieempfänglichkeit beim Schaf. Aufgrund der niedrigen Probenzahlen kann die Relevanz dieser Kandidatengene nicht ausgeschlossen werden. Zukünftige Studien können inzwischen auf den Illumina OvineSNP50 Gen Chip zurückgreifen, um die Identifizierung Scrapie assoziierter SNPs zu ermöglichen. Dies erfordert allerdings eine ausreichende Probenzahl, um auch Assoziationen von Genorten mit mäßigem Effekt auf Scrapie Empfänglichkeit nachzuweisen. Eine Möglichkeit, um die Probenzahl zu erhöhen, wäre die Verwendung von Proben aus Scrapie DNA Banken von verschiedenen EU Ländern.
Identifikation und Charakterisierung von Polymorphismen in Kandidatengenen für Scrapie Empfänglichkeit beim Schaf
Keywords: Scrapie; Schaf; LAMR1; SCRG1; PRND; scrapie; sheep; LAMR1; SCRG1; PRND; ddc:630